Effect of Feeding Degummed Cassia tora Seed Meal in Partial Replacement of Soybean Meal in the Concentrate Mixture on Nutrient Utilization and Performance of Sahiwal Calves - Patel, Sanjay; Sehgal, J.P.; Shivani, Swati; Gautam, Mayank (Indian Journal of Animal Nutrition, 2018)
A study was conducted to investigate the effect of inclusion of different levels of Cassia tora seed meal in partial replacement of soybean meal on palatability, nutrient utilization and performance in Sahiwal calves. Sahiwal male calves (n=18) were randomly divided into three groups of 6 animals each based on their body weight and age and fed as per requirement (ICAR, 2013) for 105 days. Soybean meal was replaced by Cassia tora seed meal in the concentrate mixture at 0, 3 and 5 (% DM) in C, T1 and T2 groups, respectively. Intakes of DM, CP and TDN were similar in different groups. Also, digestibility of DM, CP, OM, EE, NDF and ADF did not differ among the groups. Nitrogen utilization and feed efficiency were also not affected on inclusion of C. tora seed meal in the concentrate mixture. Thus, Cassia tora seed meal could economically be added up to 5% replacing soybean in the concentrate mixture of Sahiwal calves without any adverse effect since its incorporation up to this level exhibited no adverse effects on nutrient intake and utilization.